Followers’ Affective Responses to Tourism Information on Instagram: A Study of the @zonakalakkaro Instagram Account - Dwi Dini Farah Diva; Khatibah (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − This study aims to understand the affective experiences of followers in responding to tourism information published through the Instagram account @zonakalakkaro. The research focuses on how visual content shapes followers’ emotional attraction, imagination, expectations, and evaluations of the tourist destinations presented. Method − This study employed a qualitative method with a phenomenological approach to explore the subjective experiences of followers when interacting with tourism-related content on the Instagram account. Data were collected through in-depth interviews with three active followers of @zonakalakkaro, observations of digital interactions on the account’s posts, and documentation of relevant tourism content. Data analysis was conducted using phenomenological procedures, including the identification of significant statements, the categorization of these statements into experiential themes, and the formulation of the essence of participants’ experiences. Findings − The findings reveal that followers’ affective experiences are formed through three main stages: emotional attraction to the visual representation of tourist destinations, the development of imagination and expectations regarding tourism experiences, and emotional evaluation after comparing digital representations with the actual conditions of the destinations. Furthermore, the analysis of followers’ comments indicates that most responses reflect positive emotional experiences, such as admiration, interest, comfort, and a desire to visit the featured destinations. These findings suggest that social media functions not only as a medium for disseminating tourism information but also as a space for constructing emotional experiences that influence users’ perceptions and interests toward tourist destinations.